Building Star Trek [videorecording (DVD)] - Grogan, Mick; Conrad, Jim (Narrator) (Smithsonian Channel, 2016)
Against the backdrop of two ambitious projects: rebuilding the bridge and restoring the original USS Enterprise model, a who's who of astronauts, engineers, writers, innovators, as well as the series' stars come together to explore the visionary universe of Star Trek, revealing how one little television show has truly, boldly gone where no show has gone before.